Implementation Of SWOT Analysis Of Marketing Information Systems Based Website On Tongs Media - Munir, Muhammad Syahrul (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The purpose of this study is to find out and explain the development of information systems as a sales medium at Tongs Media in terms of SWOT analysis. This study uses a qualitative paradigm by using case studies. The findings in this study are the marketing strategy, especially the marketing information system implemented by Tongs Media, which includes several strategies, which include picking up the ball strategy, building a network, providing excellent service, and providing satisfactory service. So that this research can provide a SWOT analysis design for marketing information systems so that researchers can find out and can provide marketing strategies for the future. Keywords: SWOT analysis, Information System, Marketing.